2021
DOI: 10.1177/1071181321651090
|View full text |Cite
|
Sign up to set email alerts
|

Investigating a Virtual Reality Based Subterranean Scenario Examining Augmented Reality Implications for Military Operators

Abstract: Virtual and augmented reality have made it possible to test new technologies for military missions - such as using augmented reality to support complicated subterranean (sub-t) missions. The military will soon offer operators the ability to wear augmented reality (AR) head-mounted displays (HMDs) while conducting missions. Therefore, it is crucial to understand how this emerging technology will positively and negatively impact Soldiers’ ability to execute missions. This paper describes the development of a vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…But, other human-machine systems might also benefit from creating a separate layer or map of how information "works" in the system. A variant and extension of DTA and ITA is our method of Dynamic Information Needs Analysis (DINA) -see Zamen, Drake, et al (2021) and Zamen, Roeca, et al (2021).…”
Section: Other Types Of Task Analysismentioning
confidence: 99%
“…But, other human-machine systems might also benefit from creating a separate layer or map of how information "works" in the system. A variant and extension of DTA and ITA is our method of Dynamic Information Needs Analysis (DINA) -see Zamen, Drake, et al (2021) and Zamen, Roeca, et al (2021).…”
Section: Other Types Of Task Analysismentioning
confidence: 99%
“…Using virtual reality simulations, they were able to simulate realistic situations and gather feedback to improve the design and effectiveness of AR interfaces in these critical public safety contexts. Furthermore, Zaman et al [25] conducted a study focused on the usability of AR technology in combat missions. They used virtual reality simulations during subterranean operations to investigate the usability aspects of AR interfaces.…”
Section: Virtual Reality Simulations For Evaluation Of Ar Warningsmentioning
confidence: 99%
“…In the context of roadway work zone safety, a few studies [21], [22], [23] have utilized VR to explore worker behavior across different contexts and technological settings. Also, some studies within healthcare and military sectors [24], [25], [26] have reported the use of AR simulations within VR environments. However, a critical question is the extent to which VR-simulated AR can effectively mimic the complexities of real-world dynamics and accurately record reaction times in the context of safety within roadway work zones.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work using VEs to support interface design research has investigated how data should be presented through HUDs to support operators' needs in high-stakes environments. For instance, Zaman et al (2021) used VR to examine the utility of a prototype AR-based display to support military subterranean operations. The display provided navigation information to support wayfinding during a simulated search and rescue mission.…”
Section: Introductionmentioning
confidence: 99%